Nevlasne mova is straight in Novel M. Kotsyubinsky (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article highlights peculiarities of using inner represented speech in Kotsybinskiy’s stories. Inner represented speech is defined as a stylistic device reflecting thoughts and feelings going on in the character’s mind. The author of the article identifies such communicative types of inner represented speech as monologue and dialogue.
Keywords: nevlasne mova is straight; straight navlasne dіalog; nevlasne direct monologue